In vitro immune modulation by antibodies coupled to tumour cells. - Darling, D; Galea-Lauri, J; Gäken, J; Towner, P; Kuiper, M; Hollingsworth, S; Hirst, W; Barnard, A; Buggins, A; Mufti, G; Farzaneh, F (1997)
Modification of autologous tumour cells to express the immune costimulator B7.1 is a potential strategy for immunotherapy of cancer. Previously, this has involved introduction of genetic material into cells, in vitro culture, and confirmation of the protein product on the cell surface. This is possible only if sufficient tumour is obtainable and efficiently modified in a short time. Whilst progress has been made on ex vivo tumour cell culture and transfection/infection procedures there are still tumour types for which the present means of gene transfer are not efficient enough. We describe a highly efficient in vitro procedure for the modification of over 99% of the cells in a population, allowing the expression of cell surface proteins with potential immune modulatory activities. This procedure, which can be completed in as little as 24 h with no upper limit on cell number, utilizes succinimide esters to label cell surface proteins with biotin covalently. Biotinylated cell membrane proteins then anchor an avidin bridge for immobilizing protein G'-biotin. This can serve to bind immunoglobulin (Ig) molecules via their Fc region such that the variable region of the antibody is freely and functionally available. In the present study the binding of a stimulatory mouse anti-human CD28 monoclonal antibody to the surface of tumour cells is used to show that the modified cells are capable of co-stimulating T cells in vitro. The simplicity of the method, and the use of common reagents, represents a further step towards a realistic, truly 'off-the-shelf', nongene immunotherapy protocol.